Electrical & Mechanical Fault Alert Traffic Light System Using Wireless Technology - Sivarao, Subramonian; Siva Kumar, Subramaniam; Mazran , Esro; T., Joseph Sahaya Anand (IJENS Publishers, 2010)
An innovative idea has been devised into a beta prototype of traffic light electrical and mechanical fault detection system. This system alerts via wireless technology to the respective personnel to get them fixed immediately upon improper electrical malfunctions or mechanical damages are detected. This invention would be the best instantaneous solution to ensure all traffic lights are repaired immediately in making sure the road accidents at junctions are reduced dramatically. Detailed SMS including the traffic light pole ID #, street, town and also fault occurrence time will be sent to the respective personnel to take immediate corrective actions. Once the fault has been fixed, wok completed message will also be sent to the higher authority for work completion validation.